2018
DOI: 10.1037/fsh0000328
|View full text |Cite
|
Sign up to set email alerts
|

A review of published guidance for video recording in medical education.

Abstract: This review organizes potential threats to patients' rights for those medical educators who use video recording technology. The review reveals a need for broader consensus about video recording guidelines and for research on video recording practices, especially given technological advances in video equipment and the expansion of video technology in health care settings. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Some have also argued that HIPAA regulations may not apply to activities related to provider education. 23 In the current study, staff concerns were also perceived as important by current and future users (median score 4[3e5] on 5point Likert scale). Previous work by Davis et al 25 found that video review can be associated with anxiety, especially among attending physicians.…”
Section: % Ofmentioning
confidence: 76%
See 1 more Smart Citation
“…Some have also argued that HIPAA regulations may not apply to activities related to provider education. 23 In the current study, staff concerns were also perceived as important by current and future users (median score 4[3e5] on 5point Likert scale). Previous work by Davis et al 25 found that video review can be associated with anxiety, especially among attending physicians.…”
Section: % Ofmentioning
confidence: 76%
“…Around the time of this study was the implementation of the Health Information Portability and Accountability Act (HIPAA) of 1996, which introduced medicolegal and patient privacy concerns surrounding the use of TVR. 23 While HIPAA establishes national standards for the protection of health information, hospital administrations have continued difficulty interpreting and applying the law. HIPAA allows for the use of data collection, research initiatives and performance and quality improvement programs.…”
Section: Discussionmentioning
confidence: 99%
“…Ample literature has touched upon the various ethical and legal considerations surrounding video recording outlining the storage of the content, withdrawal of consent, ownership, and distribution of the video. 8,9 The cast members should be briefed beforehand about the video and their role in it.…”
Section: Preparation and Equipmentmentioning
confidence: 99%
“…To consider implications of the study findings, one needs to address the feasibility of using video recordings in training and education. Potential risks to patients’ rights have been examined and organized into six categories: informed consent policies, informed consent procedures, recorded medical errors, secondary use of recordings, collateral patient information, and public trust issues ( 11 ). An additional concern may be the medicolegal aspects in the event of a complication ( 12 ).…”
mentioning
confidence: 99%